Microspectroscopic analysis of the X-ray-induced photoreduction in Fe-and Mn-containing SMMs - Schmidt, Norman Anja; Scheurer, Andreas; Sperner, Stefan; Fink, Rainer (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2010)
Scanning transmission X-ray microspectroscopy (STXM) and L-edge near-edge X-ray absorption fine structure (NEXAFS) spectroscopy have been applied to study the valence states of metal ions in various Fe-and Mn-containing single-molecule magnet materials, in particular the ligand-stabilized metal complexes NaFe (so-called "ferric wheel"), Fe (so-called "ferric star") and Mn (so-called "manganese wheel"). We compare dose-dependent L-edge absorption spectra with the results of theoretical studies of the involved metal ions to conclude on the change in oxidation state upon increasing the X-ray dose. It is found that even low-intensity irradiation induces the reduction of the weakly interacting metal ions, and that the soft X-ray-induced photoreduction is less pronounced in microcrystalline films. © 2010 Verlag der Zeitschrift für Naturforschung, Tübingen.
Keywords: Single-molecule Magnet (SMM); X-Ray Absorption; X-Ray Microspectroscopy; STXM; Photoreduction